Heterotriangulene-based unsymmetrical squaraine dyes: synergistic effects of donor moieties and out-of-plane branched alkyl chains on dye cell performance - Karjule, Neeta; Munavvar, Fairoos M. K.; Nithyanandhan, Jayaraj (Journal of Materials Chemistry A, 2016)
Unsymmetrical squaraine sensitizers with two different donor moieties, triphenylamine (NSQR) and heterotriangulene (NSQ1–3), for dye-sensitized solar cells (DSSCs) have been designed and synthesized. These dyes utilize the indolium moiety to control charge recombination dynamics at the TiO2-dye-electrolyte interface by connecting linear and branched alkyl functionalities. In the present study, an efficient heterotriangulene (HT) donor and a branched alkyl group at sp3-C atoms were strategically incorporated to increase the power conversion efficiency (PCE) of zwitterionic dyes by improving photo-current density (Jsc) and open-circuit potential (Voc) of the cell. Among these four dyes, NSQ3 exhibited the highest efficiency of 6.73% with a Jsc of 18.74 mA cm−2, Voc of 0.53 V, and fill factor (ff) of 68.3%, without any co-adsorbent under an irradiance of 100 mW cm−2 (simulated AM 1.5G sunlight). In the presence of 3α,7α-dihydroxy-5β-cholanic acid (CDCA), NSQ1, NSQ2 and NSQ3 showed an efficiency of 7.07%, 7.38% and 7.17%, respectively. Despite the low Voc, far red light harvesting efficiency, reduced dye aggregation, long lifetime (τ) of injected electrons and high quantum efficiency of NSQ1–3 played constructive roles in achieving high PCE efficiency. Deceleration of charge recombination for NSQ dye cells was further studied by electrochemical impedance spectroscopy (EIS) and open-circuit photo-voltage decay (OCVD) measurements.